PENGARUH PERENDAMAN LARUTAN TEH TERHADAP DAYA TETAS TELUR IKAN LELE SANGKURIANG (Clarias gariepinus) - Ahmad Baharudin; M Bahrus Syakirin; Tri Yusufi Mardiana (Fakultas Perikanan Universitas Pekalongan, 2017)
This study aims to determine the effect of the tea solution to the hatching of fish eggs catfish and determine the percentage of the optimal solution for soaking tea fish eggs catfish. The study was designed using completely randomized design (CRD) by applying 5 treatments and 3 replications. As the treatment is tea solution at a dose as follows: A (0 g / L), B (2 g / L), C (4 g / L), D (6 g / L) and E (8 g / L). Results of analysis of variance showed differences in the percentage of tea very significant effect on the percentage of hatchery fish catfish. The average percentage of hatchery fish catfish highest obtained at treatment of 6 g / L is 76.67%, then treatment of 8 g / L at 63.33%, the treatment of 4 g / L by 60%, the treatment of 2 g / L of 53.33% and lowest on the treatment of 0 g / L at 43.33%. The results of the analysis of polynomials orthogonal indicates that the response percentage of hatchery fish catfish to the difference in the percentage of tea quadratic equation: Y = 41.4286 + 8.4031 X - 0.6548 X2, where the percentage of tea optimal for 6:42% with the percentage of hatchery fish catfish of 68.39%. Keywords : Hatcing rate, tea, catfish